MODEL INQUIRY LEARNING DAN MINAT MEMBACA DALAM PEMBELAJARAN MENULIS CERITA PENDEK - Amin Yusuf (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2018)
The research on the ability of writing short stories is very important because writing is one of language competence that students must have. The skill of writing short stories is quite difficult to master due to its complexity and some factors that obstruct its learning process, like an ineffective learning model. For that reason, the appropriate method should be applied in the learning process. It uses a 2 x 2 (two-by-two) factorial design of experimental research method. The population in this research is 10th grade students of SMA Negeri 3 Samarinda. Based on the data analysis, it shows that (1) there is skill difference in writing short stories between students who have studied learning models of inquiry learning and two stay two stray, (2) there is skill difference in writing short stories between students who have high and low reading interests, and (3) there is an interaction between the teaching model and reading interest and the skills of writing short stories.